THE EFFECT OF SHOPPING MALLâS ATTRIBUTES TOWARD CUSTOMER SATISFACTION OF ABC Mall AND XYZ Mall - Astono, Cynthia (iBuss Management, 2014)
With the tight competition among shopping malls in Surabaya, it lead towards the concept war between them to stay longer within the industry. Currently, there are two shopping malls, which are in the middle of tight competition; they are ABC Mall and XYZ Mall. Although ABC MallÂ is the newest entrant of shopping mall in Surabaya,Â XYZ MallÂ as the old player is still developing. Thus, this research aims to analyze and find out which shopping mallsâ attribute that able to increase the customer satisfaction. There are five shopping mallâs attributes, they are convenience, mallâs environment, tenant presence, service quality, and marketing focus. From those five attributes, 156Â questionnaire data collected by using simple random sampling and analysed using multipleÂ linear regression method, results findings shows that four out of five attributes show significant effect toward customer satisfaction. They are convenience, mallâs environment, service quality, and marketing focus. Â Keywords: Mall, Attributes, Shopping, Customer Satisfaction.